Erk2 Phosphorylation of Drp1 Promotes Mitochondrial Fission and MAPK-Driven Tumor Growth - Kashatus, Jennifer A.; Nascimento, Aldo; Myers, Lindsey J.; Sher, Annie; Byrne, Frances L.; Hoehn, Kyle L.; Counter, Christopher M.; Kashatus, David F. (Molecular cell, 2015)
Ras is mutated in up to 30% of cancers, including 90% of pancreatic ductal adenocarcinomas, causing it to be constitutively GTP-bound, and leading to activation of downstream effectors that promote a tumorigenic phenotype. As targeting Ras directly is difficult, there is a significant effort to understand the downstream biological processes that underlie its protumorigenic activity. Here, we show that expression of oncogenic Ras or direct activation of the MAPK pathway leads to increased mitochondrial fragmentation and that blocking this phenotype, through knockdown of the mitochondrial fission-mediating GTPase Drp1, inhibits tumor growth. This fission is driven by Erk2-mediated phosphorylation of Drp1 on Serine 616, and both this phosphorylation and mitochondrial fragmentation are increased in human pancreatic cancer. Finally, this phosphorylation is required for Ras-associated mitochondrial fission, and its inhibition is sufficient to block xenograft growth. Collectively, these data suggest mitochondrial fission may be a target for treating MAPK-driven malignancies. [Display omitted] •Drp1 is required for xenograft growth•MAPK promotes mitochondrial fragmentation through Drp1•Erk2 phosphorylates Drp1 to promote mitochondrial fission•Drp1 S616 phosphorylation is required for mitochondrial fission and tumor growth Mitochondrial function is important for the growth of tumors driven by oncogenic Ras or the MAPK pathway. Kashatus et al. demonstrate that activation of these pathways leads to Mek-dependent phosphorylation of the GTPase Drp1 and subsequent mitochondrial fragmentation. They further demonstrate that inhibition of Drp1 or its phosphorylation blocks tumor growth.